2020
DOI: 10.1111/jcmm.15120
|View full text |Cite
|
Sign up to set email alerts
|

TAT‐dextran–mediated mitochondrial transfer enhances recovery from models of reperfusion injury in cultured cardiomyocytes

Abstract: Acute myocardial infarction is a leading cause of death among single organ diseases.Despite successful reperfusion therapy, ischaemia reperfusion injury (IRI) can induce oxidative stress (OS), cardiomyocyte apoptosis, autophagy and release of inflammatory cytokines, resulting in increased infarct size. In IRI, mitochondrial dysfunction is a key factor, which involves the production of reactive oxygen species, activation of inflammatory signalling cascades or innate immune responses, and apoptosis.Therefore, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 59 publications
0
35
0
2
Order By: Relevance
“…In recent years, various methods have been developed to artificially introduce isolated exogenous mitochondria into cells ( Table 2). These methods, using cell penetrating peptides (CPPs) [7], centrifugal force [8], magnetic force [9], and vapor bubbles [10], successfully and more efficiently internalized exogenous mitochondria into cells. Putative intracellular trajectory of exogeneous internalized mitochondria, which originate from either isolated or exosome-derived mitochondria.…”
Section: Artificial Mitochondrial Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, various methods have been developed to artificially introduce isolated exogenous mitochondria into cells ( Table 2). These methods, using cell penetrating peptides (CPPs) [7], centrifugal force [8], magnetic force [9], and vapor bubbles [10], successfully and more efficiently internalized exogenous mitochondria into cells. Putative intracellular trajectory of exogeneous internalized mitochondria, which originate from either isolated or exosome-derived mitochondria.…”
Section: Artificial Mitochondrial Transfermentioning
confidence: 99%
“…Maeda et al designed the Trans-Activator of Transcription protein (TAT) conjugated with dextran to enable complex formation and isolated mitochondria with TAT-dextran, which allowed easier penetration of the plasma membrane through the reduction of the net negative charges, and the properties of CPP and TAT, independent of macropinocytosis, demonstrated that the complex can more efficiently transfer exogenous mitochondria into cells [7]. The improvement of the transfer efficiency was verified by using primary rat neonatal cardiomyocytes that were exposed to oxidative stress based on the survival and the reduced apoptosis signals following stress.…”
Section: Cell Penetrating Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…However, low transfer efficiency is a challenge in clinical settings. In the neonatal rat cardiomyocytes (NRCMs) with IRI, the use of transactivator of transcription dextran complex (TAT-dextran) enhanced the uptake of mitochondria into rat cardiomyocytes and protected the cardiomyocytes ( Maeda et al, 2020 ). The enhanced transfer of mitochondria to NRCMs can significantly reduce the apoptosis of cardiomyocytes after oxidative stress and prevent the inhibition of OXPHOS in mitochondria.…”
Section: Intercellular Mitochondrial Transfer Provides a Protective Mmentioning
confidence: 99%
“…Horizontal transfer of genetic materials is a common characteristic of bacteria such as E. coli; however, these phenomena are also observed in mammalian cells (Pace et al, 2008). Since mammalian horizontal transfer of mitochondria through a tunneling nanotube was reported in an in vitro experiment (Rustom et al, 2004), mitochondrial transfer has been demonstrated with various mechanisms, such as nanotube (Islam et al, 2012), extracellular vesicles (Hayakawa et al, 2016), and macropinocytosis (Kitani et al, 2014), as well as by using an artificial device (Wu et al, 2016) and a compound (Maeda et al, 2020a). Although the efficiency of mitochondrial transfer did not dominate over the pre-existing mtDNA but provided an additive functionality in the host cells, mechanistic insights of mitochondrial transfer with respect to cell entry and endosomal escape have been deepened (Kami & Gojo, 2020).…”
Section: Introductionmentioning
confidence: 99%